2017
DOI: 10.1038/nrc.2017.105
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin ligases in oncogenic transformation and cancer therapy

Abstract: The cellular response to external stress signals and DNA damage depends on the activity of ubiquitin ligases (E3s), which regulate numerous cellular processes, including homeostasis, metabolism and cell cycle progression. E3s recognize, interact with and ubiquitylate protein substrates in a temporally and spatially regulated manner. The topology of the ubiquitin chains dictates the fate of the substrates, marking them for recognition and degradation by the proteasome or altering their subcellular localization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
300
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 380 publications
(302 citation statements)
references
References 211 publications
(300 reference statements)
1
300
0
1
Order By: Relevance
“…The above statements suggested that RNF38 was an oncogenetic protein in many tumors. E3 ligases can transfer ubiquitin to substrates for their degradation in the ubiquitin-proteasome system, and are crucial for mediating the degradation of short-lived regulatory proteins including many oncogene products and tumor suppressors [27][28][29]. In this study, we found that RNF38 interacted with SHP-1 and induced its polyubiquitination for degradation, which suggested that RNF38 was a novel E3 ligase for SHP-1 ubiquitination (Figs 2 and 3).…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…The above statements suggested that RNF38 was an oncogenetic protein in many tumors. E3 ligases can transfer ubiquitin to substrates for their degradation in the ubiquitin-proteasome system, and are crucial for mediating the degradation of short-lived regulatory proteins including many oncogene products and tumor suppressors [27][28][29]. In this study, we found that RNF38 interacted with SHP-1 and induced its polyubiquitination for degradation, which suggested that RNF38 was a novel E3 ligase for SHP-1 ubiquitination (Figs 2 and 3).…”
Section: Discussionmentioning
confidence: 56%
“…E3 ligases can transfer ubiquitin to substrates for their degradation in the ubiquitin-proteasome system, and are crucial for mediating the degradation of short-lived regulatory proteins including many oncogene products and tumor suppressors [27][28][29]. E3 ligases can transfer ubiquitin to substrates for their degradation in the ubiquitin-proteasome system, and are crucial for mediating the degradation of short-lived regulatory proteins including many oncogene products and tumor suppressors [27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…(6) At present, no actionable target is available to counteract EMT, whereas highly proliferative tumors often present alterations of genes involved in cell-cycle checkpoints, chromatin remodeling, and DNA repair, against which several targeted approaches have been developed in the last 20 years. (7) A main novelty in the article by Hooks et al is the identification of bortezomib as a putative new drug for HB therapy. The researchers focused their attention on the C2A HB type and found an FA-related signature consisting of overexpression of FANCD2, FANCI, and BRCA1 genes.…”
Section: See Article On Page 89mentioning
confidence: 99%
“…EMT is a well‐established cellular process often associated with tumor resistance to genotoxic treatments and indicated as a cancer stem cell hallmark . At present, no actionable target is available to counteract EMT, whereas highly proliferative tumors often present alterations of genes involved in cell‐cycle checkpoints, chromatin remodeling, and DNA repair, against which several targeted approaches have been developed in the last 20 years …”
mentioning
confidence: 99%
“…Ever since the discovery of ubiquitin (Ub) four decades ago (Ciehanover, Hod, & Hershko, 1978), this small protein has been linked to multiple cellular processes, including cell proliferation, development, immune responses, and numerous human diseases including cancer (Calistri, Munegato, Carli, Parolin, & Palu, 2014;Dantuma & Bott, 2014;Senft, Qi, & Ronai, 2018;Zinngrebe, Montinaro, Peltzer, & Walczak, 2014). Indeed, protein ubiquitination, the process of attaching Ub and poly-Ub chains to cellular substrates, is an integral and essential part of the cell machinery, and serves to modify, regulate, and degrade proteins ( Fig.…”
Section: Introductionmentioning
confidence: 99%